Unfair Contract Terms in Malaysian Islamic Banks: Empowering Bank Consumers by Islamic Financial Literacy via Selected Ethical Framework - Noor Mahinar Abu Bakar; Rusni Hassan; Ng See Teong (Journal of Islamic Finance, 2024)
For too long, Malaysian bank consumers have been at the losing end due to unfair contract terms that are disproportionately biased favoring the Islamic banks and they have no alternative but to accept those detrimental terms or risk having their financing application be rejected. However, bank consumers seldom read the standard form contracts that Islamic banks offer before signing them. This paper aims to explore the role of Islamic financial literacy in educating bank consumers to avoid unfair contract terms in Islamic banking contracts. Adopting the qualitative method through content and comparative analysis methodology, this study provides an exploratory analysis on selected ethical literacy framework based on Maqasid al-Shariah to help integrate literacy to bank consumers which include Islamic education ethics, Maqasidic leadership model, Multidimensional model and Madani ethical framework introduced by the 10th Prime Minister of Malaysia, Anwar Ibrahim. Findings of this study conclude that the no reading problem of the standard form banking contracts by bank consumers could be improved by adopting Maqasidic Islamic financial literacy ethics. These Maqasidic Islamic literacy ethics empower bank consumers to apply their duty to read and be responsible to report unfair contract terms to Bank Negara Malaysia. This study suggests Islamic Banks to practice sustainable consumer banking by drafting fair contracts and strike out detrimental contract terms since responsible treatment to bank consumers ensure and generate banking growth. This study is important to government policy since sustainable and ethical banking practices on bank consumers help generate growth in the Islamic banking sector in Malaysia.